Factors Affecting on the Prostate Volume for Yemeni Healthy Adults using Ultrasound in Sana'a city - Al-Awer, Salah Al-deen et al. (University of Science and Technology, Sana'a, Faculty of Medicine and Health Sciences, Radiology and Medical Imaging Technology Program, 2023)
This research describe the factors affecting on prostatic volume and assessment the average volume for Yemeni healthy adults and to know normal curve increment of prostatic volume according to factors affecting on prostatic volume. The exam was done by the radiologists in (UST hospital, UST medical complex and Al-Kuwait hospital) in the duration of February – April 2018. About 97 patients were randomly selected, aged from 18 years and above, whom have no any symptoms related to prostate pathologies. Transabdominal ultrasound scanning by 3.5 MHz probes was performed, and the maximum height, width, and depth of their prostate diameters were obtained, as well as their prostate volumes.